In search of 'home' in the transnational imaginary: food, roots, and routes in memoirs by Asian Australian women writers - Ahmad, Siti Nuraishah; Ramlan, Wan Nur Madiha (2018)
Food is one of the cultural goods that travel in the global networks of diaspora. It conveys notions and memories of home, community and identity for those living in two (or more) locations. In diasporic and/or transnational writing, the preparation and consumption of food often appear as a way of maintaining or examining one’s ties with the homeland. This paper takes the memoirs of two Asian Australian women writers, Beth Yahp’s Eat First, Talk Later (2015) and Alice Pung’s Unpolished Gem (2006) as the basis for a study of how food is deployed in the writers’ search for ‘home’. Yahp’s memoir of “food, family and home” explores how food and memories of eating mediate her sense of ‘home’ as a person who is designated an Other in her homeland of Malaysia. In Alice Pung’s memoirs, food acts as metaphor for her unease and anxiety as an Asian Australian growing up in a homeland that does not quite embrace her. Avtar Brah’s study of ‘home’ in the context of diaspora and recent studies of food in diasporic fiction and cultural studies provide the concepts which this paper employs in reading Yahp and Pung’s memoirs.